Wild Cats Diversity and Activity Patterns in Bukit Baka Bukit Raya National Park, Kalimantan, Indonesia - Persada Agussetia Sitepu; Juliarta Bramansa Ottay; Gusti Wicaksono; Rusnadi; Firasadi Nursub’i; Risky Ananda Kurniawan; Utin Riesna Afrianti; Tomi Ariyanto (Universitas Nasional Jakarta, 2025)
Kalimantan is home to five species of wild cats, but scientific information about them is still limited. This study aims to examine the biodiversity, spatial distribution, relative abundance, activity patterns, and occupancy rate of wild cats in the Belaban Resort, Bukit Baka Bukit Raya National Park (BBBR NP). Data collection was conducted from March 2024 to August 2025 at 25 camera trap (CT) stations, which were operated for a total 6.756 trap-nights. The analysis includes calculation of the relative abundance index, occupancy, distribution, and activity patterns. A total 45 independent events of wild cats from three species were recorded, namely the sunda clouded leopard, leopard cat and marbled cat. The leopard cat has the highest relative abundance (5,01 events per 100 trap-nights). The sunda clouded leopard showed the highest occupancy probability (ψ = 0,794), while the marbled cat had the lowest abundance and occupancy. The spatial distribution showed that 60% of the camera stations recorded at least one species of wild cat, with two stations at elevation of 520-762 meters above the sea level recording to the highest detections, in line with the high presence of potential prey. There findings underscore the importance of maintaining forest cover, increasing area patrols, and involving the community in controlling hunting and encroachment as part of area management planning. Overall, the results of this study provide a scientific basis for the implementation of adaptive conservation and the strengthening of management strategies to ensure the sustainability of wild cat populations in the Belaban Resort, BBBR NP